조현병 스펙트럼 장애의 1년 유지 치료에서 클로자핀과 병용 치료제의 처방 양상 분석 - 김재원; 김세현; 장진혁; 문선영; 강태욱; 김민아; 권준수; Kim, Jaewon; Kim, Se Hyun; Jang, Jin-Hyeok; Moon, Sun-Young; Kang, Tae Uk; et al. (Journal of the Korean Society of Biological Psychiatry, 2021)
Objectives Clozapine is the most effective atypical antipsychotic agent for the treatment-resistant schizophrenia (TRS), however, only 40%-70% of TRS patients respond to clozapine. Moreover, TRS encompasses various symptom dimensions. Therefore, augmentation with other medications for clozapine is frequently applied. However, the prescription pattern of clozapine and combined medications in Korea is yet to be examined. This study aims to investigate the maintenance treatment pattern of clozapine and augmentation agents in one Korean tertiary hospital. Methods The patients with schizophrenia spectrum disorders under clozapine maintenance, defined as one-year clozapine continuation, were subjected for analysis. Medication data at one-year time-point after clozapine initiation was extracted and analyzed. Results Among total 2897 patients having clozapine prescription experience from January 2000 to December 2018, 1011 patients were on clozapine maintenance. The mean age of clozapine initiation was 30.2 ± 11.3 years, and the maintenance dose of clozapine was 217.8 ± 124.3 mg/day. Combination rate of antipsychotics, mood stabilizers, and antidepressants were 43.5%, 25.3%, 38.6%, respectively. Most frequently prescribed drugs in each category were aripiprazole, valproate, and sertraline. Olanzapine equivalent dose of combined antipsychotics was 10.4 ± 7.7 mg/day. Male patients were prescribed higher dose of combined antipsychotics and higher rate of antidepressants. Female patients had later onset of clozapine prescription. Patients with two or more combined antipsychotics were prescribed higher dose of clozapine and higher rate of antidepressants compared to patients with one combined antipsychotic. Conclusions Taken together, among the patients taking clozapine, a substantial rate of patients were under polypharmacy. The present findings based on the real-world prescription pattern could provide the valuable clinical information on the treatment of TRS-related conditions.